Posted by **Manmeet singh** on Wednesday, August 2, 2006 at 10:58am.

If cosec A – sin A=a3 , sec A – cos A =b3 , prove that

a2 b2 (a2 + b2)=1

Since the first two equations involves two constants a3 and b3, one cannot prove the third equation with totally different constants a2 and b2. Is a3 supposed to be a-cubed and a2 supposed to be a-squared?

If a2 is supposed to be a-squared and a3 is supposed to be a-cubed, please use ^2 to denote second power and ^3 to denote third power, etc., and use that notation in future questions that you may sumbit.

## Answer This Question

## Related Questions

- Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x=...
- GENRAL MATHS - PROVE THAT (1+COT A+TAN A)(SIN A-COS A)=SEC A\COSEC A-COSEC A\SEC...
- Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...
- maths - prove that sin A(1+tan A)+cos A(1+cot A)= sec A+ cosec A
- Maths - prove that the equation of straight line which passes through the point...
- trig help much appreciated! :)) - 1. Find the complete exact solution of sin x...
- trigonometry help me - 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin ...
- math - if 0<A<90 and Sin A+ cos A+ tan A+cot A+sec A+cosec A =7 then prove...
- MATH - Hi, I really need help with these questions. I did some of them halfway, ...
- trignonmetry - 6. Prove that tan λ cos^2 λ + sin^2λ/sin λ = ...

More Related Questions